The Dependent Coverage Mandate Took a Bite Out of Crime - Zachary S. Fone; Andrew I. Friedson; Brandy Lipton; Joseph J. Sabia (Institute of Labor Economics (IZA), 2020)
The Affordable Care Act's Dependent Coverage Mandate (DCM) induced approximately two million young adults to join parental employer-sponsored health insurance (ESI) plans. This study is the first to explore the impact of the DCM on criminal arrests, a potentially important externality. Using data from the National Incident-Based Reporting System, we find that the DCM induced an 11 percent reduction in criminal incidents involving arrestees ages 19 to 25, driven by property crime declines. An examination of the underlying mechanisms suggests that declines in large out-of-pocket expenditures for health care, increased educational attainment, and increases in parent-adult child cohabitation may explain these crime declines. Back-of-the-envelope calculations suggest that the DCM generated approximately 3.1 billion in annual social benefits from crime reduction.
Keywords: I13; I18; K14; 330; Affordable Care Act; Dependent Coverage Mandate; crime; arrests